2018
DOI: 10.1016/j.cobeha.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition, maintenance, and therapeutic use of a simple motor skill

Abstract: Operant conditioning of the spinal stretch reflex (SSR) or its electrical analog, the H-reflex, is a valuable experimental paradigm for studying the acquisition and maintenance of a simple motor skill. The CNS substrate of this skill consists of brain and spinal cord plasticity that operates as a hierarchy—the learning experience induces plasticity in the brain that guides and maintains plasticity in the spinal cord. This is apparent in the two components of the skill acquisition: task-dependent adaptation, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Furthermore, in rats with incomplete spinal cord injury, inappropriate conditioning (i.e., down-conditioning the soleus Hreflex to further weaken stance) did not further impair locomotion [39]. The absence of deleterious effects is likely to reflect appropriate compensatory plasticity; and it is in accord with the negotiated equilibrium model of spinal cord function [177,178,182]. Third, in a person with impaired motor function, appropriate reflex conditioning can trigger wider beneficial plasticity [41].…”
Section: Spinal Reflexes As Therapeutic Targetsmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, in rats with incomplete spinal cord injury, inappropriate conditioning (i.e., down-conditioning the soleus Hreflex to further weaken stance) did not further impair locomotion [39]. The absence of deleterious effects is likely to reflect appropriate compensatory plasticity; and it is in accord with the negotiated equilibrium model of spinal cord function [177,178,182]. Third, in a person with impaired motor function, appropriate reflex conditioning can trigger wider beneficial plasticity [41].…”
Section: Spinal Reflexes As Therapeutic Targetsmentioning
confidence: 88%
“…The reflex changes gradually over days and weeks due to plasticity in both the brain and the spinal cord. This plasticity appears to comprise a hierarchy in which the plasticity in the brain induces and maintains the plasticity in the spinal cord [43,175,176] (reviewed in [42,177,178]). Figure 2 illustrates the operant conditioning protocol for the human soleus H-reflex [33].…”
Section: Spinal Reflexes As Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, there is no agreement in the literature about the number of fMV sessions required for motor improvement to be very effective. Since the amount of the induced change grows gradually as conditioning trials continue over subsequent days and weeks ( 35 , 36 ) we decided to carry out a total of 12 fMV sessions (3 sessions per week for 4 consecutive weeks), thereby extending the classic one-week treatment (overall 3 sessions) ( 13 , 19 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…When considering ADSP in the ventral spinal cord networks that generate locomotor and postural commands, the term "activity" may lead to some confusion as it could refer to "movement" or "training" instead of the "rate of action potential firing" in presynaptic neurons. Several recent reviews have reported the numerous plastic changes (morphological changes, axonal sprouting, …etc) induced by motor activities as well as by motor task learning in the spinal motor networks under both physiological and pathophysiological conditions (see for examples [3][4][5]). However, although interacting functionally through overlapping elements, a distinction should be made between the overall impact of the neuronal activity generated during training or learning and the continuous and dynamic integration of firing rate that occurs in synaptic connections.…”
mentioning
confidence: 99%